Increased Posterior Cingulate Functional Connectivity Following 6-Month High-Dose B-Vitamin Multivitamin Supplementation: A Randomized, Double-Blind, Placebo-Controlled Trial - Downey, Luke A.; Simpson, Tamara N.; Ford, Talitha C.; McPhee, Grace; Suo, Chao; Myers, Stephen P.; Oliver, Chris; Stough, Con K. K. (Frontiers in Nutrition, 2019)
B vitamins are essential for optimal brain and body function, and are particularly important for cortical metabolic processes that have downstream effects on mitigating oxidative stress. Oxidative stress has been linked to poor psychological outcomes including psychological distress, which has wide-reaching implications for the community and the workplace. Given work-related stress has been associated with poor mental health outcomes, high-dose B vitamin supplementation may be effective in improving brain function and psychological outcomes via attenuation of oxidative stress. This randomized, double-blind, placebo-controlled study investigated psychological outcomes following 6-month supplementation of a high-B-vitamin multivitamin in a large sample of healthy adults (n = 108, aged 30–70 years), as well as changes in default mode network functional connectivity in a subset of the original sample (n = 28). Improvements in occupational stress, general health, perceived stress, depressive symptoms, and mood profiles were identified for both active and placebo groups over time (p < 0.05 corrected). Seed-based functional connectivity analysis centered on the posterior cingulate cortex (PCC) showed that connectivity between the PCC and the caudate increased for the active treatment group, but decreased for the placebo group (p < 0.05 corrected). These findings reveal a substantial intervention effect for both active and placebo treatments, which could in part be associated with a placebo effect in subjective measures. There was, however, a significant treatment effect in the objective measure of functional connectivity, suggesting that reduced psychological stress and high-B-vitamin multivitamin supplementation may lead to an increase in DMN and caudate functional connectivity, which might reflect a strengthening of neurocircuitry within areas associated with reward and emotion at rest. Future studies should consider a placebo run-in methodology to reduce the placebo effect on the subjective measures of stress.